2021
DOI: 10.5853/jos.2021.00850
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Etiology and Outcomes after Endovascular Thrombectomy: Results from the SITS Registry and a Meta-Analysis

Abstract: Background and Purpose The influence of stroke etiology on outcomes after endovascular thrombectomy (EVT) is not well understood. We aimed to investigate whether stroke etiology subgrouped as large artery atherosclerosis (LAA) and cardiac embolism (CE) influences outcomes in large artery occlusion (LAO) treated by EVT.Methods We included EVT treated LAO stroke patients registered in the Safe Implementation of Treatment in Stroke (SITS) thrombectomy register between January 1, 2014 and September 3, 2019. Primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
1
14
1
Order By: Relevance
“…In our study, almost half (46%) of the patients undergoing MT had concomitant AF, similar to other studies ( 2 ), stressing that this is a very frequent clinical scenario. Obviously, patients with AF are likely to receive OAC, if AF was known before stroke.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, almost half (46%) of the patients undergoing MT had concomitant AF, similar to other studies ( 2 ), stressing that this is a very frequent clinical scenario. Obviously, patients with AF are likely to receive OAC, if AF was known before stroke.…”
Section: Discussionsupporting
confidence: 91%
“…Atrial fibrillation (AF) causes ~20% of all acute ischemic stroke (AIS) cases ( 1 ), and 40% of large-vessel occlusion patients with AIS who undergo mechanical thrombectomy (MT) have a clinical history of AF ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…We only enrolled AIS-LVO patients with LAA etiology in this study given the difficulty in achieving recanalization during EVT in AIS-LVO patients with LAA etiology ( 15 , 16 ). Results from the Safe Implementation of Treatment in Stroke (SITS) thrombectomy register indicated a lower chance of reperfusion and worse outcomes after thrombectomy in patients with LAA compared to cardiac embolism etiology ( 34 ). Previous studies have found that intra-arterial thrombolysis can increase recanalization and improve clinical outcomes ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…BAO patients with in situ atherosclerotic thrombosis had significantly worse clinical outcomes and lower successful recanalization rates compared with BAO patients who had embolism without artery steno-occlusion 34. Matusevicius et al studied 7543 patients who underwent EVT, and showed that stroke patients with large artery atherosclerosis had lower successful reperfusion rates and worse functional outcomes than stroke patients with cardioembolism 35. In addition, several studies have shown that the cerebellar infarct volume before EVT was also a predictor of clinical outcomes in BAO patients 36–38.…”
Section: Discussionmentioning
confidence: 99%